TRADITION OF OPIUM USE IN BLORA DURING THE DUTCH INDIES GOVERNMENT - Novi Rochmadani; Irma Ayu Kartika Dewi (Vol. 2 No. 1 (2024): Proceeding of International Conference on Cultures & Language 2024, 2024)
Opium is a basic ingredient for making medicine from the sap of young opium fruit. In ancient times, it was widely consumed by people as a cultural mixture for drinking tea or coffee, cigarettes, and can also be used for medicinal purposes. In this research, the rearchers want to know how Opium first entered Blora, what was behind the development of Opium in Blora in 1870-1940, what was the tradition of using Opium in Blora in 1870-1940. The method used in this research is the historical research method. The methods used are heuristics, criticism, interpretation and historiography. Collecting related sources, researchers searched the Dinas Kearsipan Dan Perpustakaan Provinsi Jawa Tengah, Dinas Kearsipan Daerah Blora, and UNS Library. Verification step by comparing the contents of the sources to find the validity of the data and take a reliable source. Interpretation is the tradition of consuming Opium in the Blora community with the help of a socio-economic approach that is relevant to the research object. Historiography is writing resulting from research. The results of this research explain that since 1870, opium trading companies brought by ethnic Chinese via small fishing boats from the Jepara area have entered the Blora area via Kudus. The tradition of smoking opium was very popular among the people of Blora at the end of the 19th century because it contained an addictive substance which was able to relieve fatigue and was believed by people such as farmers, artists and labor heads to maintain their fitness. The people of Blora have a tradition of consuming low quality Opium by extracting it in the form of medicine, mixing it with kitchen spices, mixing it in cigarette tobacco, mixing it with flavorings in tea or coffee drinks. The working community believes that opium has many useful properties for reducing body aches, but in the long term it can be harmful to health. In 1930 the Dutch East Indies government strictly issued regulations ranging from trade to Opium consumption. The people of Blora often consume opium using the traditional Tike method, namely a low content of opium extract mixed with syrup and sugar solution with added Awar-Awar leaves or often brewed into coffee.